Dakwah Islam dan Nasionalisme: Studi Kasus Dakwah Kebangsaan A.R. Baswedan (Islamic Da'wah and Nationalism: A Case Study of Nationalism Da'wah of A.R. Baswedan) - Agus Riyadi; Zulfikar Ganna Priyangga; Mustolehudin Mustolehudin (Jurnal Dakwah Risalah, 2021)
This article aims to find out the national da'wah carried out by A.R. Baswedan. This research uses a character study approach with a literature study method. The results showed that the national da'wah carried out by A.R. Baswedan broadly fits the indicators of the national mission. The indicators of national preaching carried out by A.R. Baswedan can be seen from the aspects used in da'wah, namely; based on Pancasila, UUD 1945, Bhineka Tunggal Ika, and adherence to the Unitary State of the Republic of Indonesia. In addition, da'wah also accommodates differences in background, gender, ethnicity and class. This paper suggests the need for inclusive preaching carried out massively by preachers throughout the archipelago, so that the cultivation of a strong ideology, especially related to the preaching of rahmatan lil 'alaimin and soothing the Indonesian nation and not clashing with political interests.